Strategies to Increase Independent Prosperous Graduation Family Hope Program Recipients in Central Lampung Regency - Lilis Suryati S; Kordiyana K Rangga; Yaktiworo Indriyani; Wuryaningsih Dwi Sayekti; Yuniar Aviati Syarief; Tubagus Hasanuddin (International Journal Labs, 2023)
Independent prosperous graduation is a benchmark for the performance of social companions and an indication of the success of the Family Hope Program (PKH), so a strategy is needed to increase independent prosperous graduation. This study aims to analyze strategies to increase independent prosperous graduation of PKH recipients. Data collection was carried out from September 2022 to February 2023 with informants as many as 12 PKH social assistants in Central Lampung Regency. The data analysis method used is SWOT analysis. The results showed that the strategies for increasing independent prosperous graduations in Central Lampung Regency include: holding regular meetings of all PKH Central Lampung human resources to unify perceptions about independent prosperous graduates, maximize the abilities and skills possessed by PKH social assistants to become facilitators, educators, motivators and advocates for PKH KPM; optimizing the role of PKH district coordinators in encouraging the success of independent prosperous graduates; maximizing the role of PKH social assistants to identify KPM business potential and empower according to existing potential to increase KPM prosperous graduation; ; utilizing support from various resource systems to develop the potential of KPM PKH both in terms of business and education of KPM PKH children; conduct training to improve the skills of PKH social assistants on KPM graduating techniques; utilizing the Family Improvement Meeting (P2K2) as a forum to change the mindset and behavior of KPM; and coordinate with village and sub-district officials.